Exuberant case of erythema elevatum diutinum in a patient infected with HIV and hepatitis B virus, - Sayuri Aparecida Hirayama; Cezar Arthur Tavares Pinheiro; Isabelle Maffei Guarenti; Danise Senna Oliveira
Abstract Erythema elevatum diutinum is a small vessel vasculitis which is benign, rare, and chronic. It is clinically characterized by violaceous, brown, or yellowish plaques, nodules, and papules. It has been associated with autoimmune, infectious, and neoplastic processes. The following case describes a patient with hepatitis B virus and human immunodeficiency virus with CD4 count < 200 mm3, HIV-seropositive for 16 years, and diagnosed with hepatitis B virus at the hospital. The patient was treated with oral dapsone 100 mg/day, showing regression after seven months of treatment. The authors found three cases in the literature of association of erythema elevatum diutinum, human immunodeficiency virus, and hepatitis B virus.